2008
DOI: 10.1016/j.chom.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A Stable Prefusion Intermediate of the Alphavirus Fusion Protein Reveals Critical Features of Class II Membrane Fusion

Abstract: Summary Alphaviruses infect cells via a low-pH-triggered membrane fusion reaction mediated by the class II virus fusion protein E1, an elongated molecule with three extramembrane domains (DI–III). E1 drives fusion by inserting its fusion peptide loop into the target membrane and refolding to a hairpin-like trimer in which DIII moves toward the target membrane and packs against the central trimer. Three-dimensional structures provide static pictures of prefusion and postfusion E1 but do not explain this transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
90
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 32 publications
11
90
0
Order By: Relevance
“…This agrees with the postfusion trimer structure, which demonstrates packing of DIII into the groove formed between two E1 proteins in the trimer (14). While it is possible that dimers are generated during the core trimer assembly process, our electron microscopy studies of DI/DII membrane interactions have not detected dimers (40,49). Thus, our current and previous data strongly support the idea that the initial DIII target is a membrane-inserted extended E1 trimer.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This agrees with the postfusion trimer structure, which demonstrates packing of DIII into the groove formed between two E1 proteins in the trimer (14). While it is possible that dimers are generated during the core trimer assembly process, our electron microscopy studies of DI/DII membrane interactions have not detected dimers (40,49). Thus, our current and previous data strongly support the idea that the initial DIII target is a membrane-inserted extended E1 trimer.…”
Section: Discussionsupporting
confidence: 79%
“…In the presence of excess DIII, the E1 intermediate exhibited neither SDS nor trypsin resistance, presumably reflecting a complete block in fold-back of endogenous DIII. Previous in vitro experiments showed that DIII binds to trimers of E1 DI/II proteins but not to monomers (40). This agrees with the postfusion trimer structure, which demonstrates packing of DIII into the groove formed between two E1 proteins in the trimer (14).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Sanchez-San Martin et al reported that the E1 envelope from Semliki Forest virus, was found to associate with membranes in an in vitro assay in its truncated (soluble) form by forming clusters of five and six trimers (49). Of more importance, using a combination of x-ray crystallography and cryo-EM, Gibbons et al found that the same E1 protein in Semliki Forest virus forms a ring of five trimers along the fivefold axis in an early step of membrane fusion, before the formation of a fusion pore or channel (48).…”
Section: Bivalent Antibody Bindingmentioning
confidence: 99%